AS A SYSTEM OF PREPARING FUTURE TEACHERS FOR SOCIAL PEDAGOGICAL ACTIVITY BASED ON SOCIAL TECHNOLOGIES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The pedagogical training of future teachers primarily depends on the quality of training of pedagogical personnel in higher educational institutions. The level of competence, professional skills, and ability to correctly and purposefully manage pedagogical processes of specialists determine the success of the formation of the student's personality. This poses an urgent task for the entire system of higher pedagogical education, as well as for all organizations responsible for education and personnel training, to further study the issues of professional training of future teachers in organizing and managing the processes of raising a harmonious personality.